Exciton-driven antiferromagnetic metal in a correlated van der Waals insulator - Carina A. Belvin (Nature Portfolio, 2021)
Previous work has shown the existence of spin-orbit-entangled excitons and their coupling to antiferromagnetism in the correlated insulator NiPS3. Here the authors show that non-equilibrium driving of these excitons produces a transient metallic antiferromagnetic state that cannot be achieved by tuning the temperature in equilibrium.